2008
DOI: 10.1016/j.placenta.2007.07.003
|View full text |Cite
|
Sign up to set email alerts
|

A Placental Cause of Intra-uterine Fetal Death Depends on the Perinatal Mortality Classification System Used

Abstract: A placental cause of intra-uterine fetal death depends on the perinatal mortality classification system used Korteweg, F.J.; Gordijn, S.J.; Timmer, Albertus; Holm, J.P.; Ravise, J.M.; Erwich, Jan Jaap H. M. Take-down policy If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim. Abstract Different classification systems for the cause of intra-uterine fetal death (IUFD) are used internationally. About… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
56
0
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(69 citation statements)
references
References 29 publications
8
56
0
5
Order By: Relevance
“…Al Kadri etal found that women that did not receive ANC are at 70 % risk of IUFD. It is 25 fold higher in women with placental abruption, tenfold higher in Babies with IUGR and three fold higher with PIH [7].According to Kotweg etal the single most important cause for IUFD was growth restriction, emphasizing the importance of placental role in optimal fetal growth [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Al Kadri etal found that women that did not receive ANC are at 70 % risk of IUFD. It is 25 fold higher in women with placental abruption, tenfold higher in Babies with IUGR and three fold higher with PIH [7].According to Kotweg etal the single most important cause for IUFD was growth restriction, emphasizing the importance of placental role in optimal fetal growth [8].…”
Section: Discussionmentioning
confidence: 99%
“…Lack of antenatal care is directly related to the socioeconomic and educational level of women. Health education toward stressing the importance of antenatal care, ante partum screening for congenital malformations and selective pregnancy terminations, patient compliance and vigilant monitoring will reduce a number of preventable fetal deaths [8].…”
Section: Discussionmentioning
confidence: 99%
“…For establishing the cause of death we used the Tulip classification for perinatal mortality that separates cause, mechanism, and risk factors that are often mixed in other systems. 31 Having strict criteria, the Tulip classification system itself influenced our adjudication of causes and judgment as to whether tests were valuable. Not all possible tests are needed to classify cause of death in the Tulip classification.…”
Section: Korteweg Fetal Death Workup Am J Obstet Gynecol 2012 (Conmentioning
confidence: 99%
“…Infections, problems related to the placenta and umbilical cord, congenital anomalies, maternal [11]. A number of investigations, including autopsy, examination of the placenta, amniocentesis and tests on blood from the mother and child, have been recommended in the diagnostic evaluation of IUFD [12][13][14][15]. The proportion of IUFDs in which no identifiable cause can be determined ranges from 12 to 50% and may be related to environmental factors [16][17][18].…”
Section: Discussionmentioning
confidence: 99%